2009
DOI: 10.1073/pnas.0808798106
|View full text |Cite
|
Sign up to set email alerts
|

Disentangling prenatal and inherited influences in humans with an experimental design

Abstract: Exposure to adversity in utero at a sensitive period of development can bring about physiological, structural, and metabolic changes in the fetus that affect later development and behavior. However, the link between prenatal environment and offspring outcomes could also arise and confound because of the relation between maternal and offspring genomes. As human studies cannot randomly assign offspring to prenatal conditions, it is difficult to test whether in utero events have true causal effects on offspring o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
120
0
4

Year Published

2009
2009
2017
2017

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 124 publications
(135 citation statements)
references
References 35 publications
9
120
0
4
Order By: Relevance
“…Further control of genetic or familial risk could be provided by the use of within-family studies comparing siblings born to the same woman (particularly before and after significant weight loss), by Mendelian randomization, 57 and (or) the examination of the offspring of women who conceived using certain assisted reproductive technologies. 58 While such observational data will be helpful in further establishing this link, a clear demonstration of causal effects requires the use of experimental approaches. While it is challenging to effect lasting weight loss, experimental studies done in humans and aimed at examining strategies to reduce pre-pregnancy obesity could potentially be used to assess the cognitive, emotional, and behavioural outcomes of the offspring of these gestations and compare them to control groups.…”
Section: Discussionmentioning
confidence: 99%
“…Further control of genetic or familial risk could be provided by the use of within-family studies comparing siblings born to the same woman (particularly before and after significant weight loss), by Mendelian randomization, 57 and (or) the examination of the offspring of women who conceived using certain assisted reproductive technologies. 58 While such observational data will be helpful in further establishing this link, a clear demonstration of causal effects requires the use of experimental approaches. While it is challenging to effect lasting weight loss, experimental studies done in humans and aimed at examining strategies to reduce pre-pregnancy obesity could potentially be used to assess the cognitive, emotional, and behavioural outcomes of the offspring of these gestations and compare them to control groups.…”
Section: Discussionmentioning
confidence: 99%
“…Roza et al [40] demonstrated that the relationship between MSP and child behavior problems was fully accounted for by family socioeconomic status and parental psychopathology. Convincing evidence for the role of inheritable pathways was reported by Rice et al [41] , comparing the association between MSP and antisocial behavior in the offspring of mothers who were either biologically related or unrelated to their child as a result of in vitro fertilization. The authors concluded that the relationship was entirely explained by inherited pathways, as the offspring of mothers who smoked during pregnancy and were biologically related to their child were at higher risk for conduct problems, while such an effect was not found in the offspring of mothers who smoked during pregnancy but were biologically unrelated to their child [41] .…”
Section: Discussionmentioning
confidence: 99%
“…Convincing evidence for the role of inheritable pathways was reported by Rice et al [41] , comparing the association between MSP and antisocial behavior in the offspring of mothers who were either biologically related or unrelated to their child as a result of in vitro fertilization. The authors concluded that the relationship was entirely explained by inherited pathways, as the offspring of mothers who smoked during pregnancy and were biologically related to their child were at higher risk for conduct problems, while such an effect was not found in the offspring of mothers who smoked during pregnancy but were biologically unrelated to their child [41] . Based on a longitudinal twin study, it was concluded that around half of the observed association between MSP and young children's conduct problems was attributable to correlated genetic effects [42] .…”
Section: Discussionmentioning
confidence: 99%
“…Um estudo recentemente publicado exemplifi ca a necessidade de compreendermos o mecanismo através do qual um fator supostamente ambiental atua 23 . Existe uma longa e ainda não resolvida discussão na literatura em relação ao mecanismo através do qual a exposição intraútero ao tabaco levaria à psicopatologia nas crianças.…”
Section: Entendendo O Mecanismo De Ação Dos Agentes Causaisunclassified
“…Há evidências que apontam que tal mecanismo se daria através de ação sobre o ambiente intraútero, enquanto outros estudos indicam que fumar durante a gestação é um marcador de psicopatologia materna associada a fatores genéticos que, por sua vez, são herdados pelas crianças, levando então à psicopatologia 24 . Rice et al 23 23 . O peso de nascimento foi menor no grupo de crianças expostas ao tabaco intraútero, independentemente de serem geneticamente relacionadas ou não às suas mães.…”
Section: Entendendo O Mecanismo De Ação Dos Agentes Causaisunclassified